A Journey to Disillusionment - Mazari, Sherbaz Khan (New York Oxford University Press, 1999)
Chronicle of political history of Pakistan; memoirs of a prominent Pakistani politician from 1964-1988.
Include Illustrations and Index
Keywords: Politicians -- Mazari, Sherbaz Khan -- Politics and government -- Pakistan